How important is the N-terminal acetylation of alpha-synuclein for its function and aggregation into amyloids? - Iyer, Aditya; Sidhu, Arshdeep; Subramaniam, Vinod (Frontiers in Neuroscience, 2022)
N-α-acetylation is a frequently-occurring post-translational modification in eukaryotic proteins. It has manifold physiological consequences on the regulation and function of several proteins, with emerging studies suggesting that it is a global regulator of stress responses. For decades, investigations into the precise role of the intrinsically disordered protein alpha-synuclein (αS) in the etiology of Parkinson's disease (PD) overlooked the N-α-acetylation of αS. That the N-terminus of α-synuclein is acetylated is now without question, but in turn, has led to more unanswered questions. Is N-α-acetylation of αS a constitutive modification akin to most cellular proteins, or is it regulated? Is N-α-acetylation of αS relevant to the as-yet elusive function of αS? How does the N-α-acetylation of αS influence the aggregation of αS into amyloids? Here, we provide an overview of the current knowledge and discuss prevailing hypotheses on the impact of N-α-acetylation of αS on its conformational, oligomeric, and fibrillar states. The extent to which N-α-acetylation of αS is vital for its function, membrane binding, and aggregation into amyloids is also explored here. We further discuss the overall significance of N-α-acetylation of αS for its functional and pathogenic implications in Lewy body formation and synucleinopathies.